An Improved Rotating Restart Method for a Sensorless Permanent Magnet Synchronous Motor Drive System Using Repetitive Zero Voltage Vectors - Seo, Dong Woo; Bak, Yeongsu; Lee, Kyo Beum (IEEE Transactions on Industrial Electronics, 2020)
This paper presents an improved rotating restart method for a sensorless permanent magnet synchronous motor (PMSM) drive system using repetitive zero voltage vectors. To restart the sensorless PMSM drive system, a method for estimating initial rotor position and speed is required due to the absence of sensors such as encoders and resolvers. The rotor position and speed can be estimated using the short-circuit current vectors generated by applying zero voltage vectors. However, the estimated rotor position and speed can be inaccurate. The inaccurate rotor position that causes the current is distorted by the back-electromotive force of the PMSM, and it is impossible to precisely control the system. Therefore, an improved rotating restart method for the sensorless PMSM drive system using repetitive zero voltage vectors is proposed. The effectiveness of the proposed method is verified through simulation and experimental results using a 5-kW PMSM drive system.
Keywords: Active neutral point clamped; Back electromotive force; Initial rotor position; Permanent Magnet Synchronous Motor; Restart method; Rotor position; Sensorless permanent magnet synchronous motor; Zero voltage vectors; Active neutral-point-clamped (ANPC) inverter; permanent-magnet synchronous motor (PMSM); repetitive zero voltage vectors; rotating restart method; sensorless control